A Preseason Training Program With the Nordic Hamstring Exercise Increases Eccentric Knee Flexor Strength and Fascicle Length in Professional Female Soccer Players - Karoline Baptista Vianna; Lívia Gonçalves Rodrigues; Nathalia Trevisol Oliveira; João Breno Ribeiro-Alvares; Bruno Manfredini Baroni (North American Sports Medicine Institute, 2021)
# Background Training programs that include the Nordic hamstring exercise (NHE) have been shown to increase eccentric knee flexor strength and biceps femoris fascicle length in male athletes. However, the effect of NHE on female athletes remains unknown. # Purpose To investigate the collective and individual responses of professional female soccer players engaged in a preseason training program with the NHE regarding eccentric knee flexor strength and biceps femoris long head fascicle length. # Study Design Quasi-experimental study. # Methods Sixteen amateur female soccer players (without a NHE training routine) were evaluated 8-weeks apart to: (1) assess reliability of eccentric knee flexor strength and biceps femoris fascicle length measures; and (2) determine the typical error of measures that would be used to discriminate training responders and non-responders. The NHE training group had 17 professional female soccer players who performed an 8-week training program with the NHE during preseason. Within-group analysis was performed with paired sample t-tests (pre- vs. post-training), and individual responses were determined using the typical error criteria. # Results The non-trained group's data demonstrated that measures of strength (ICC=0.82-0.87, typical error = 12-13 N) and fascicle length (ICC=0.92-0.97; typical error = 0.19-0.38 cm) were reliable. In the NHE training group, both limbs increased the eccentric knee flexor strength (\~13%; ES=0.74-0.82) and the biceps femoris fascicle length (\~6%; ES=0.44-0.65). Twelve players (\~71%) were considered responders to the NHE training program for the eccentric knee flexor strength, while eight athletes (\~47%) were responders for the biceps femoris fascicle length. # Conclusion The 8-week preseason training program with the NHE increased both eccentric knee flexor strength and biceps femoris fascicle length in professional female soccer players. More than two-thirds of players demonstrated a meaningful increase in eccentric strength, while nearly half achieved consistent fascicle length increases with the NHE training.